Дон-Кихоты «Cнежной революции». Рец. на кн: «“Мы не немы!”: Антропология протеста в России 2011–2012 годов» [Don Quixotes of the “Snow Revolution”: “My ne nemy!”: Antropologiia protesta v Rossii 2011—2012 godov. A Review Article - Darja Dorving (Slavica Revalensia)
This review article is focussed on a recently published book analyzing various forms of the protest discourse in Russia during the winter of 2011—2012.